Benzoyl esters and flavones from the leaves of Polyalthia parviflora - Minh Hang, Nguyen Thi; Tu Oanh, Nguyen Thi; Hue, Cao Thi; Tung, To Hai; Thoa, Ha Thi; Thanh, Le Nguyen; Giap, Tran Huu; Hung, Nguyen Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Two benzoyl esters, benzyl 2,6-dimethoxybenzoate (1), benzyl 2,5-dihydroxybenzoate (2), together with three flavones, 5-hydroxy-3,4’,7-trimethoxyflavone (3), 3,5-dihydroxy-4’,7-dimethoxyflavone (4) and 5,6-dihydroxy-3,4’,7-trimethoxyflavone (5), were isolated from the ethyl acetate extract of Polyalthia parviflora leaves. Their structures were elucidated on the basis of spectroscopic analysis and comparisons with related known compounds